Tinjauan Perspektif ’Urf terhadap Tradisi Larangan Pernikahan Dandang Rebutan Penclokan di Desa Senden Peterongan Jombang - Andrias Wahyu Pratama; Mochamad Samsukadi; Mahmud Huda (Lembaga Yasin AlSys, 2026)
Although Islam has clearly regulated the provisions of marriage, some members of the community in Senden Village, Peterongan Subdistrict, Jombang Regency, continue to maintain the dandang rebutan penclokan marriage prohibition tradition, which prohibits two siblings from marrying partners from the same village because it is believed to bring misfortune. This study aims to analyze the status of this tradition from the perspective of ‘urf in Islamic law. The study employed a qualitative approach with a case study design. Data were collected through interviews, observation, and documentation and were then analyzed using qualitative descriptive analysis through the stages of data reduction, data presentation, and conclusion drawing. The results show that the dandang rebutan penclokan tradition constitutes ‘urf khāṣṣ because it applies only to the community of Senden Village and contains the social value of maintaining harmonious relationships between families. However, the belief that violating this tradition inevitably causes financial hardship, misfortune, or death is categorized as ‘urf fāsid because it contradicts the Islamic creed, which affirms that sustenance, marriage partners, and death are determined by Allah the Almighty. This study concludes that local traditions may be preserved as part of community wisdom provided that they are not accompanied by beliefs that contradict Islamic law. These findings contribute to the development of Islamic legal studies that proportionally accommodate local culture while providing guidance for the community in distinguishing the social values of tradition from beliefs that contradict Islamic principles.